Amyloid precursor-like protein 2 expression in macrophages: differentiation and M1/M2 macrophage dynamics - Brumfield, Gabrielle L.; Knoche, Shelby M.; Doty, Kenadie R.; Larson, Alaina C.; Poelaert, Brittany J.; Coulter, Don W.; Solheim, Joyce C. (Frontiers in Oncology, 2025)
Amyloid precursor-like protein 2 (APLP2) has been previously associated with pro-tumor phenotypes in cancer cells, and in this current study we investigated the expression and functions of this protein in macrophages. Our findings showed that APLP2 expression was increased in monocyte-like U937 cells after cytokine-induced differentiation to macrophage-like cells. Evaluation of human mRNA data revealed that APLP2 is more highly expressed in human M2/anti-inflammatory (pro-tumor) macrophages than in M1 macrophages (which have a pro-inflammatory, anti-tumor phenotype). Consistent with the mRNA data, by immunoblotting we identified increased APLP2 protein expression in mouse M2/anti-inflammatory macrophages. Intratumoral infiltration of M2/anti-inflammatory macrophages has been reported in several cancers, including neuroblastoma (NB). We observed that treatment of macrophages with NB-conditioned media induced M2/anti-inflammatory and mixed phenotypes. Through comparison of macrophages from wild-type and APLP2-knockout mice, we correlated alterations in inflammation-associated markers with the presence of APLP2. This suggests that APLP2 influences macrophage polarization dynamics between M0/unpolarized and pro- and anti-inflammatory states, and populations altered by APLP2 KO resemble the macrophage profiles altered with NB-conditioned media treatment. In total, our work implicates APLP2 as a mediator of macrophage status, namely in the M0/unpolarized macrophage and the M1/pro-inflammatory and M2/anti-inflammatory axis.